Beyond Beauty: Enhancing Cosmetology Students’ Emotional Resilience Through A Wellness Community Project on Senior Citizens - Bibiana Paulus; Vienny Balakrishnan; Diana Kayunon; Alvy Wendyline Florentius; Nur Syahida Mohd Nazri; Sirhajwan Idek; Lumang Anak Lang (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
The goal of this research project was to examine the effects of service learning on 19 students’ emotional intelligence and adversity quotient which can be vital in prepping them for the real world. It was a twofold project as it also tackled the stigma on senior citizens who are often overlooked from receiving grooming treatments. Hence, a group of cosmetology students from Keningau Vocational College conducted grooming treatments comprising manicure, pedicure and massaging for the residents of an old folks’ home in Papar, Sabah. These students were required to answer two instruments that gauged their emotional intelligence and resilience technically known as adversity quotient.  The data were analyzed through descriptive statistics and Spearman’s rank Correlation Coefficient. The findings revealed that emotional intelligence was strongly correlated with adversity quotient in which the better the students were in emotional awareness, regulation and utilization, the better they could cope with pressure from challenges and conflicts. This suggests that service learning can potentially nurture students especially vocational students to be psychologically stronger.